APLIKASI PUPUK P (TSP) DAN URIN SAPI PADA TANAMAN KACANG HIJAU (Vigna radiata. L) - Agus Syafria; Siti Zahrah; Tengku Rosmawaty (UIR Press, 2013)
This research aimed to know the effect of various P fertilizer and cow urine on growth and yield of green pea. The experiment was arranged in th completely randomized design with cow factors. The first factor was Fertilizer TSP (P), consisting of 4 factors namely P0 (without fertilizer), P1 (10 g/plot), P2 (15 kg/plot), and P3 (20 kg/plot). The second factor was cow urine, consisting of 4 factors, i.e. U0 (without cow urine), U1 (50 cc/l water), U2 (100 cc/l water), and 150 cc/l water). The observed parameters were plant height, flowering age, harvest age, number of pods per plant, percentage of full pod per plant, dry grain weight per plant, dry 100 grain, and harvest index. The interaction between P (TSP) fertilizer and cow urine had a significant effect on plant height, number of pods per plant, and dry grain weight per plant. The best treatment was the usage of TSP fertilizer with dosage of 10 g/plot and cow urine with concentration of 100 cc/l water. The effect of P fertilizer was significant on plant height, lowering age, harvest age, number of pods per plant, percentage of full pod per plant, dry grain weight per plant and dry weight of 100 grain with the best treatment was the usage of TSP fertilizer with dosage of 10 g/plot. Furthermore, the effect of cow urine was also significant on plant height, flowering age, harvest age, pod number per plant, percentage full pod per plant, dry weight per plant, and dry weight of 100 grain with the best treatment of the usage of cow urine with concentration of 100 cc/l water. The interaction as well as alone, the application of TSP fertilizer and cow urine had no a significant effect on harvest index of green pea.